1985
DOI: 10.1172/jci111787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of immunoglobulin and specific antibody levels in twins reared apart.

Abstract: We studied the effect of the same genetic but different environmental factors on total immunoglobulin and specific antibody levels in twins reared apart. Sera were analyzed from 26 monozygotic (MZ) and 10 dizygotic (DZ) twin pairs, who were separated on average 2 mo after birth and reared apart. Total IgM, IgG, and IgA were measured by single radial diffusion. Specific antibodies of each isotype to tetanus toxoid, and to polyvalent and type 14 pneumococcal capsular polysaccharides were measured by a solid-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…6 Multitudinous environmental factors including infections, smoking and chemical compounds can contribute to this variation. [7][8][9] Reports of pedigree studies or twin studies 10,11 have shown that genetic factors are more important than environmental exposures in determining serum immunoglobulin level in human. 12,13 The values of genetic heritability was h 2 ¼ 0.617 þ 0.020 for IgG.…”
Section: Introductionmentioning
confidence: 99%
“…6 Multitudinous environmental factors including infections, smoking and chemical compounds can contribute to this variation. [7][8][9] Reports of pedigree studies or twin studies 10,11 have shown that genetic factors are more important than environmental exposures in determining serum immunoglobulin level in human. 12,13 The values of genetic heritability was h 2 ¼ 0.617 þ 0.020 for IgG.…”
Section: Introductionmentioning
confidence: 99%
“…Families share environmental as well as genetic factors. In a comparison of monozygotic and dizygotic twin pairs, genetic rather than environmental factors were found to control levels of immunoglobulin and specific antibodies to tetanus toxoid or pneumococcal polysaccharide [40]. However, the nature of these genetic factors differs for different antibody responses.…”
Section: Discussionmentioning
confidence: 95%
“…In general, humoral immune responses to specific antigens are influenced to variable degrees by environmental and genetic factors [Allansmith et al, 1969;Klaff and Hijmans, 1969;Kohler et al, 1985;Dunlap et al, 1993;Konradsen et al, 1993]. Twin studies in West Africa have shown that this applies also to specific immune responses against various defined epitopes of the malaria antigens RESA (ring-infected erythrocyte surface antigen), MSA-1 (merozoite surface antigen 1), MSA-2, and antigens of the sporozoite and sexual stages [Sjöberg et al, 1992;Jepson et al 1997].…”
Section: Introductionmentioning
confidence: 99%